Which Factors Drive Rental Depreciation Rates for Office and Industrial Properties?. Issue 3 (1st July 2016) - Crosby, Neil; Devaney, Steven; Nanda, Anupam
Abstract : As new buildings are constructed in response to changes in technology or user requirements, the value of the existing stock will decline in relative terms. This is termed economic depreciation and it may be influenced by the age and quality of buildings, amount and timing of expenditure, and wider market and economic conditions. In this paper, we examine why individual assets experience different depreciation rates, applying panel regression techniques to 375 office and industrial assets in the United Kingdom. The results suggest that rental value depreciation rates reduce as buildings get older, while a composite measure of age and quality provides more explanation of depreciation than age alone. Furthermore, economic and local real estate market conditions are significant in explaining how depreciation rates change over time.